Electrolyte and battery
Patent Information
- Application Number
- CN202380014446.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-02-28
AI Technical Summary
Semi-solid state batteries and solid-state batteries have low conductivity, resulting in poor rate performance, limiting their application in the new energy field.
An electrolyte with good lithium ion conductivity was developed, its specific crystallization properties were determined by X-ray diffraction pattern analysis, and a polymer formed by polymerization including the first monomer and/or the second monomer, as well as lithium salts and The electrolyte composed of organic solvents improves conductivity and thermal stability.
The battery has achieved good discharge performance at different magnifications and temperatures, significantly improved the rate performance and temperature characteristics, and especially showed excellent performance at large magnifications and low temperatures.
Smart Images

Figure CN119547243A_ABST
Abstract
Description
Electrolyte and battery Technical Field
[0001] The present application belongs to the field of batteries and relates to an electrolyte and a battery. Background Art
[0002] With the rapid development of new energy, lithium-ion batteries are in urgent need of high energy density and high safety performance. Compared with traditional liquid batteries, semi-solid-state and solid-state batteries have the advantages of high safety performance and a wide electrochemical window. They are more able to meet the high safety performance and high energy density requirements of lithium-ion batteries, and have broader application prospects in new energy fields such as cutting-edge consumer electronics, electric vehicles, and energy storage devices.
[0003] Semi-solid batteries and solid-state batteries also contain positive and negative electrodes and isolation membranes like liquid batteries. The difference is that semi-solid batteries use semi-solid electrolytes, solid-state batteries use solid electrolytes, and liquid batteries use liquid electrolytes. However, compared with liquid electrolytes, semi-solid electrolytes and solid-state electrolytes generally have the defect of lower electrical conductivity, resulting in poor battery rate performance, which limits the use of semi-solid batteries and solid-state batteries.
[0004] Summary of the Invention
[0005] The present application provides an electrolyte having good lithium ion conductivity, and a battery comprising the electrolyte has good rate and high and low temperature performance.
[0006] The present application also provides a battery, which includes the above-mentioned electrolyte and has good discharge performance at different temperatures and different rates.
[0007] In a first aspect, the present application provides an electrolyte, wherein the electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in an X-ray diffraction pattern, where M≥1 and N≥1;
[0008] Among them, 10°≤x≤30°, 30°<y≤50°;
[0009] The sum of the half-maximum widths of the M first diffraction peaks is , and the sum of the half-maximum widths of the N second diffraction peaks is b, wherein 1.0≤b / a≤1.9.
[0010] The electrolyte as described above, wherein 0.8≤a≤1.4, and 1.2≤b≤2.3.
[0011] The electrolyte as described above, wherein 1.1≤b / a≤1.28.
[0012] The electrolyte as described above, wherein the conductivity of the electrolyte is 4mS / cm to 12mS / cm, preferably, the conductivity of the electrolyte is 5mS / cm to 12mS / cm.
[0013] The electrolyte as described above, wherein the electrolyte comprises a polymer formed by polymerization of the first monomer and / or the second monomer;
[0014] The first monomer includes at least three reactive functional groups;
[0015] The second monomer includes two active functional groups.
[0016] The electrolyte as described above, wherein the first monomer includes one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives, and dipentaerythritol hexaacrylate and its derivatives.
[0017] The electrolyte as described above, wherein the second monomer is selected from one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, ethoxylated bisphenol A diacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, neopentyl glycol diacrylate and its derivatives, and 1,5-pentanediol diacrylate and its derivatives.
[0018] The electrolyte as described above, wherein the electrolyte comprises 0.05 wt% to 9 wt% of the polymer and 91 wt% to 99.5 wt% of the electrolyte solution.
[0019] The electrolyte as described above, wherein the electrolyte comprises a lithium salt and an organic solvent,
[0020] Preferably, the organic solvent comprises cyclic carbonates, linear carbonates and / or linear carboxylates.
[0021] The electrolyte as described above, wherein the weight loss rate of the electrolyte within the temperature range of 25° C. to 100° C. does not exceed 4%.
[0022] The electrolyte as described above, wherein the weight loss rate of the electrolyte within the temperature range of 25° C. to 600° C. does not exceed 84%.
[0023] The electrolyte as described above, wherein the electrolyte with a mass of M0 is heated from 25°C at a heating rate of 5°C / min, and the electrolyte is heated at a temperature of T d Mass M dMeet at least one of the following:
[0024] (1) When the temperature T d When the temperature reaches 25-100℃, the mass of the electrolyte M d ≥92.21%*M0;
[0025] (2) When the temperature T d When the temperature reaches 25℃~200℃, the mass of the electrolyte M d ≥47.63%*M0;
[0026] (3) When the temperature T d When the temperature reaches 25℃~300℃, the mass of the electrolyte M d ≥33.41%*M0;
[0027] (4) When the temperature T d When the temperature reaches 25℃~400℃, the mass M of the electrolyte d ≥25.53%*M0;
[0028] (5) When the temperature T d When the temperature reaches 25℃~500℃, the mass of the electrolyte M d ≥17.21%*M0;
[0029] (6) When the temperature T d When the temperature reaches 25℃~590℃, the mass of the electrolyte M d ≥15.54%*M0.
[0030] The electrolyte as described above, wherein the polymer is prepared by a method comprising the following steps:
[0031] performing a prepolymerization reaction on a mixed system including the first monomer and / or the second monomer at 40° C. to 60° C. and then heating the system to 80° C. to 100° C. to perform a polymerization reaction to obtain the polymer;
[0032] The prepolymerization reaction time is 0.2 h to 2 h, and the polymerization reaction time is 0.5 h to 6 h.
[0033] A second aspect of the present application provides a battery, comprising the electrolyte provided in the first aspect of the present application.
[0034] The battery as described above, wherein the battery is a semi-solid-state battery or a solid-state battery.
[0035] The battery as described above, wherein the battery is prepared by a method comprising the following steps:
[0036] performing a formation treatment on a battery system including the electrolyte to obtain the battery;
[0037] The formation treatment comprises: charging the battery system including the electrolyte to a cut-off voltage at a temperature of 60° C. to 90° C., a pressure of ≤5 MPa, and a rate of ≤0.3C.
[0038] The battery as described above also includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.
[0039] The battery as described above, wherein, further comprises a negative electrode sheet; the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises silicon, silicon carbon, SiO x , lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, copper nitride, etc.
[0040] The electrolyte of the present application has special crystallization properties, which is conducive to the conduction of lithium ions and has good electrical conductivity. It can enable the battery to have good discharge performance at different rates and temperatures, and show excellent rate performance and temperature characteristics.
[0041] The battery of the present application includes the above electrolyte and thus has excellent rate performance and high and low temperature characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] FIG1 is an X-ray diffraction pattern of the electrolyte of Example 1;
[0043] FIG2 is an X-ray diffraction pattern of the electrolyte of Example 2;
[0044] FIG3 is an X-ray diffraction pattern of the electrolyte of Example 3;
[0045] FIG4 is an X-ray diffraction pattern of the electrolyte of Example 4;
[0046] FIG5 is an X-ray diffraction pattern of the electrolyte of Example 5;
[0047] FIG6 is an X-ray diffraction pattern of the electrolyte of Example 6;
[0048] FIG7 is an X-ray diffraction pattern of the electrolyte of Comparative Example 1. DETAILED DESCRIPTION
[0049] The present application will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanations of the present application and should not be construed as limiting the scope of protection of the present application. All technologies implemented based on the above content of the present application are included within the scope of protection intended by the present application.
[0050] In a first aspect, the present application provides an electrolyte having an X-ray diffraction pattern of M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y, where M≥1 and N≥1;
[0051] Among them, 10°≤x≤30°, 30°<y≤50°;
[0052] The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.0≤b / a≤1.9.
[0053] The electrolyte of the present application is a semi-solid electrolyte or a solid electrolyte. When the electrolyte is a semi-solid electrolyte, the electrolyte includes a solid component and a liquid component, wherein the liquid component can be a liquid electrolyte conventionally used in the art, and the solid component can be a polymer; when the electrolyte is a solid electrolyte, the electrolyte at least includes a polymer.
[0054] The inventors have found that when the electrolyte of the present application is subjected to X-ray diffraction analysis, at least one first diffraction peak with a 2θ diffraction angle in the range of 10° to 30° and at least one second diffraction peak with a 2θ diffraction angle greater than 30° and not exceeding 50° will appear on the X-ray diffraction pattern, and the ratio of the sum of the half-peak widths of all second diffraction peaks to the sum of the half-peak widths of all first diffraction peaks is in the range of 1.0 to 1.9, indicating that the electrolyte has special crystallization properties, which is conducive to the conduction of lithium ions in the electrolyte, thereby making the electrolyte have good electrical conductivity, and thus the battery including the electrolyte has good discharge performance at different rates and different temperatures, showing excellent rate performance and temperature characteristics, especially more advantageous in discharging at high rates and low temperatures.
[0055] It's important to note that when performing X-ray diffraction analysis on electrolytes, especially those in batteries, the electrolytes must be pretreated after disassembly to remove other components. This pretreatment involves washing the electrolyte with deionized water, vacuuming it at 80°C for 48 hours, and testing for a moisture content of less than 1000 ppm before performing X-ray diffraction analysis.
[0056] In a specific embodiment, when 0.8≤a≤1.4 and 1.2≤b≤2.3, it is more conducive to improving the electrolyte conductivity, thereby making the battery have better rate performance and temperature characteristics.
[0057] The inventors have found that when 1.1≤b / a≤1.28, the relevant electrical properties of a battery including the electrolyte are more excellent, especially in terms of electrical conductivity, rate performance and low-temperature performance.
[0058] Furthermore, the conductivity of the electrolyte can reach 4mS / cm to 12mS / cm. Preferably, the conductivity of the electrolyte is 5mS / cm to 12mS / cm, and more preferably 7mS / cm to 12mS / cm.
[0059] In a specific embodiment, the electrolyte of the present application includes a polymer formed by polymerization of a first monomer and / or a second monomer; wherein the first monomer includes at least three active functional groups; and the second monomer includes two active functional groups.
[0060] The active functional group in this application refers to the polymerizable carbon-carbon double bond contained in the monomer. The first monomer including at least three active functional groups means that the first monomer includes at least three polymerizable carbon-carbon double bonds, and the second monomer including two active functional groups means that the second monomer includes two polymerizable carbon-carbon double bonds.
[0061] The above polymer is obtained by polymerizing the first monomer and / or the second monomer, that is, the polymer monomers of the polymer include at least one of the first monomer and the second monomer. When the polymer is obtained by copolymerizing the first monomer and the second monomer, it is beneficial to further improve the lithium ion conductivity.
[0062] In a specific embodiment, the first monomer is selected from one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives, and dipentaerythritol hexaacrylate and its derivatives.
[0063] In a specific embodiment, the second monomer is selected from one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, ethoxylated bisphenol A diacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, neopentyl glycol diacrylate and its derivatives, and 1,5-pentanediol diacrylate and its derivatives.
[0064] It should be noted that the above-mentioned derivatives refer to products obtained by replacing the original groups in the main body with new substituent groups. For example, the derivatives of ethoxylated trimethylolpropane triacrylate refer to products obtained by replacing the original groups (e.g., hydrogen atoms) in ethoxylated trimethylolpropane triacrylate with substituent groups. The present invention is not limited to the specific choice of substituent groups, and for example, the substituent groups can be at least one of halogen atoms, hydroxyl groups, thiol groups, nitro groups, cyano groups, isocyano groups, sulfone groups, hydroxylamine groups, carboxyl groups, carbonyl groups, aromatic hydrocarbons, heteroaromatic hydrocarbons, heterocycloalkyl groups, amino groups, alkoxy groups, aromatic ring oxygen groups, aromatic heterocyclooxy groups, amide groups, alkylthio groups, aromatic ring sulfur groups, heteroaromatic ring sulfur groups, silicon groups, boron groups, etc.
[0065] In a specific embodiment, the electrolyte is a solid electrolyte, which includes at least the above-mentioned polymer.
[0066] In a specific embodiment, the electrolyte is a semi-solid electrolyte, which includes 0.05 wt% to 9 wt% of a polymer and 91 wt% to 99.5 wt% of an electrolyte.
[0067] The electrolyte includes lithium salt and an organic solvent.
[0068] The lithium salt may be selected from lithium salts commonly used in the art, including but not limited to one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide, and lithium bistrifluoromethylsulfonyl imide;
[0069] The organic solvent may be an organic solvent commonly used in the art that can dissolve lithium salts.
[0070] Furthermore, the organic solvent includes cyclic carbonate, linear carbonate and / or linear carboxylate. Cyclic carbonate, linear carbonate and / or linear carboxylate constitute the non-aqueous organic solvent in the lithium salt electrolyte. The non-aqueous organic solvent can be selected from a mixture of cyclic carbonate and linear carbonate, or a mixture of cyclic carbonate and linear carboxylate, or a mixture of cyclic carbonate, linear carbonate and linear carboxylate.
[0071] Among them, the cyclic carbonate includes one or more of ethylene carbonate and propylene carbonate, the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and the linear carboxylic acid ester includes at least one of ethyl propionate, propyl propionate and propyl acetate.
[0072] In a specific embodiment, the mass content of the cyclic carbonate in the non-aqueous organic solvent is 20-60 wt %, and the mass content of the linear carbonate and / or linear carboxylate is 40-80 wt %.
[0073] Furthermore, in some specific embodiments, the electrolyte has a weight loss rate of no more than 4% within a temperature range of 25° C. to 100° C.
[0074] The mass M0 of the electrolyte is tested at the initial temperature T0 (generally room temperature 25°C), and then the temperature is increased at a certain heating rate, and the final temperature T within 100°C is d The mass of the remaining electrolyte is tested at a temperature not exceeding 100°C. The ratio of the lost mass to M0 is the weight loss rate. As the temperature continues to rise, the mass of the electrolyte continues to decrease, but the loss of the electrolyte provided in this application can be kept within a small range. Specifically, at 100°C, the weight loss rate of the electrolyte does not exceed 4%. Therefore, the electrolyte provided in this application has good thermal stability, can effectively prolong the ARC thermal runaway time in the battery, and improve the safety of the battery.
[0075] It should be noted that when performing the above-mentioned thermogravimetric analysis on the electrolyte, the electrolyte must be pretreated to remove impurities. In particular, when analyzing the electrolyte in a battery, the battery must be disassembled, the electrolyte must be rinsed with deionized water, and the solid phase components must be collected and dried at 100°C for 24 hours before thermogravimetric testing.
[0076] The thermogravimetric analysis of this application was performed using a thermogravimeter. During the test, the dried electrolyte M0 (mg) was accurately weighed and placed in an oxidized crucible. Under a nitrogen atmosphere, a Shimadzu DTG-60 differential thermal gravimetric analyzer was used. The heating rate was set to 5°C / min. The sample was heated from T0 (25°C) and the temperature at different temperatures T was collected. d The mass of the sample under x . With temperature as the horizontal axis and M x / M0 ratio is the vertical coordinate, and the thermal gravimetric curve of the electrolyte is obtained.
[0077] Furthermore, the electrolyte of the present invention has a weight loss rate of no more than 84% during a heating process from 25°C to 600°C. That is, when the electrolyte is heated from a starting temperature of 25°C (at a heating rate of 5°C / min) to 600°C, the weight loss rate of the electrolyte does not exceed 84%.
[0078] In a specific embodiment, as the temperature is increased, at least one of the following conditions is met:
[0079] (1) When the temperature T d When the temperature reaches 100℃, the mass of the electrolyte is ≥92.21%*M0;
[0080] (2) When the temperature T d When the temperature reaches 200℃, the mass of the electrolyte is ≥47.63%*M0;
[0081] (3) When the temperature T dWhen the temperature reaches 25℃~300℃, the mass of the electrolyte is ≥33.41%*M0;
[0082] (4) When the temperature T d When the temperature reaches 25℃~400℃, the mass of the electrolyte is ≥25.53%*M0.
[0083] (5) When the temperature T d When the temperature reaches 5℃~500℃, the mass of the electrolyte is ≥17.21%*M0;
[0084] (6) When the temperature T d When the temperature reaches 25℃~590℃, the mass of the electrolyte is ≥15.54%*M0;
[0085] It can be understood that the electrolyte at temperature T d The ratio of the mass of the electrolyte to M0 is the mass of the electrolyte at the current T d The quality retention rate under the current T d The quality retention rate under the current T d The sum of the weight loss rates under the following conditions is 100%.
[0086] In a specific embodiment, the polymer in the electrolyte of the present application is prepared by a method comprising the following process:
[0087] Prepolymerizing a mixed system including the first monomer and / or the second monomer at 40° C. to 60° C. and then heating the system to 80° C. to 100° C. to perform polymerization to obtain a polymer;
[0088] The prepolymerization reaction time is 0.2h to 2h, and the polymerization reaction time is 0.5h to 6h.
[0089] In addition to the first monomer and / or the second monomer, the mixed system may further include an initiator for initiating the polymerization reaction of the first monomer and / or the second monomer. Specifically, the initiator may be selected from initiators commonly used in the art, including but not limited to one or more of benzoyl peroxide, tert-butyl benzoyl peroxide, lauroyl peroxide, tert-butyl benzoyl peroxide, azobisisobutyronitrile, tert-butyl peroxyvalerate, and tert-butyl perbenzoate.
[0090] In the above preparation process, a mixed system including the first monomer and / or the second monomer is first subjected to a prepolymerization reaction at a relatively low temperature to form a polymer skeleton structure with low crystallinity, and then the prepolymer is further polymerized at a higher temperature to generate a polymer with special crystallinity properties.
[0091] The above polymer can be obtained by pre-polymerizing and polymerizing the first monomer and / or the second monomer to form a polymer, and then mixing the polymer with a lithium salt electrolyte to obtain the electrolyte of the present application. Alternatively, the first monomer and / or the second monomer can be mixed with the lithium salt electrolyte to obtain an electrolyte precursor solution, and then the first monomer and / or the second monomer can be in-situ polymerized in the electrolyte precursor solution to obtain the electrolyte of the present application.
[0092] In a second aspect of the present application, a battery is provided, which includes the electrolyte provided in the first aspect of the present application. In addition to the electrolyte, the battery of the present application further includes conventional battery components such as a positive electrode sheet, a negative electrode sheet, and a separator.
[0093] Since the battery of the present application includes the electrolyte provided in the first aspect of the present application, the battery has good discharge performance at different rates and different temperatures, showing excellent rate performance and temperature characteristics, especially having more advantages during high-rate discharge and low-temperature discharge.
[0094] Specifically, the positive electrode sheet includes a positive electrode active material layer and a positive electrode current collector. Among them, the positive electrode current collector can be selected from the positive electrode current collectors commonly used in the art, such as aluminum foil. The positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder, and an additive. Among them, the positive electrode active material can be selected from lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (Li z Ni[[ID=...]] (omitted for brevity, the translation continues as per the original structure) z O2, where x > 0, y > 0, z > 0, and x + y + z = 1), lithium nickelate (Li2NiO2), spinel lithium manganate (LiMn2O4), nickel cobalt tungsten, lithium nickel manganate, sodium-containing lithium cobaltate (Li n1-y1 Na y1 Co 1-a1-b1 M1 b1 M2 a1 O2 or Li n2-y2-b2 Na y2 Co 1-a2 M1 b2 M2 a2 O2, 0.6 ≤ n1 ≤ 0.8, 0 < y1 ≤ 0.05, 0 ≤ a1 ≤ 0.1, 0 < b1 ≤ 0.1, 0 < b1 / (1 - a1 - b1) < 0.1; 0.6 ≤ n2 ≤ 0.8, 0 < y2 ≤ 0.05, 0 ≤ a2 ≤ 0.1, 0 < b2 ≤ 0.02; M1 is selected from at least one of Te, W, Al, B, P, and K; M2 is a doping element different from M1 such as Mg, Zr, Y, La, Ni, etc.). One or more of the materials. The conductive agent, binder, and additive can all be selected from the conductive agents, binders, and additives commonly used in the positive electrode active material layer in the art, which will not be elaborated here. Further, the specific capacity of the positive electrode active material layer ≥ 160 mAh / g. Preferably, the specific capacity of the positive electrode active material ≥ 180 mAh / g.
[0095] Specifically, the negative electrode sheet includes a negative electrode active material layer and a negative electrode current collector. Among them, the negative electrode current collector can be selected from the negative electrode current collectors commonly used in the art, such as copper foil, composite copper foil, etc. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder, and an additive. Among them, the negative electrode active material can be selected from silicon, silicon carbide, SiO x(0<X<2), at least one of lithium-silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives (such as boron powder, boron oxide), aluminum and its derivatives (such as aluminum powder, lithium-aluminum alloy), magnesium and its derivatives (such as magnesium, magnesium-aluminum alloy), bismuth and its derivatives (such as bismuth, lithium-bismuth alloy), nickel and its derivatives (such as nickel, lithium-nickel alloy, lithium nickel nitride), silver and its derivatives (such as silver powder, lithium-silver alloy), zinc and its derivatives (such as zinc powder, zinc-lithium alloy, zinc nitride), titanium and its derivatives (such as titanium powder, lithium titanate, titanium dioxide, lithium-titanium alloy), gallium and its derivatives (such as gallium, lithium-gallium alloy), indium and its derivatives (such as indium powder, lithium-indium alloy), tin and its derivatives (such as tin powder, stannous oxide, tin oxide, tin sulfate), lithium nitride, copper nitride, etc. Further, the gram capacity of the negative electrode active material layer is ≥330 mAh / g, preferably ≥500 mAh / g. In a specific embodiment, the single-sided thickness of the negative electrode active material layer (the thickness of the negative electrode active material layer after rolling) is 20 μm to 110 μm, preferably 30 μm to 60 μm, such as 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 70 μm, 90 μm, 110 μm, etc.
[0096] Specifically, the separator can be selected from separators commonly used in the art, such as commercial PP separators, PE separators, and the like.
[0097] The positive electrode sheet and the negative electrode sheet can be prepared according to conventional methods in the art.
[0098] For example, in a specific embodiment, the following method is used to prepare the positive electrode sheet: after mixing the positive electrode active material, binder, conductive agent and additives, a solvent (such as N-methylpyrrolidone) is added, and the mixture is stirred under the action of a vacuum mixer until a positive electrode slurry with uniform fluidity is obtained, and the positive electrode slurry is then coated on one side or both sides of the positive electrode collector, and after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet; in a specific embodiment, the following method is used to prepare the negative electrode sheet: after mixing the negative electrode active material, binder, conductive agent and additives, a solvent (such as deionized water) is added, and the negative electrode slurry is obtained under the action of a vacuum mixer, and the negative electrode slurry is then evenly coated on one side or both sides of the negative electrode collector, and after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0099] After the positive electrode sheet and the negative electrode sheet are prepared, the positive electrode sheet, the separator and the negative electrode sheet can be placed in sequence and then wound, and an electrolyte can be added. After the steps of formation, sorting and packaging, the battery of the present application can be obtained.
[0100] Alternatively, the positive electrode sheet, separator, and negative electrode sheet may be placed in sequence and then wound, an electrolyte precursor solution may be injected, the electrolyte precursor solution may be solidified, and then the formation, sorting, and packaging processes may be performed to obtain the battery of the present application. In this preparation process, the electrolyte preparation process is completed within the entire battery system, which can simplify the preparation process.
[0101] The inventors have found that charging the battery system to the cut-off voltage for formation at a temperature of 60°C to 90°C, a pressure of ≤5 MPa, and a rate of ≤0.3C is more conducive to improving the battery rate performance.
[0102] The present application will be described in further detail below with reference to specific embodiments.
[0103] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the reagents, materials, etc. used in the following examples are all commercially available unless otherwise specified.
[0104] Example 1
[0105] The preparation method of the battery provided in this embodiment is as follows:
[0106] 1) Preparation of positive electrode
[0107] The positive electrode active material NCM811, the binder polyvinylidene fluoride, the conductive agent carbon nanotubes and the conductive carbon black were mixed in a mass ratio of 96:1.5:1:1.5, N-methylpyrrolidone was added, and the mixture was stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry was coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.
[0108] 2) Preparation of negative electrode sheet
[0109] A mixture of negative electrode active materials graphite and silicon carbon (the mixing mass ratio of graphite and silicon carbon is 4:1), a binder polyacrylic acid, a dispersant sodium carboxymethyl cellulose, a conductive agent carbon nanotubes and conductive carbon black are mixed in a mass ratio of 95:3:1:0.2:0.8, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 40%; the negative electrode slurry is coated on both sides of a copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet.
[0110] 3) Battery assembly
[0111] 3 wt % of pentaerythritol tetraacrylate, 2 wt % of ethylene glycol dimethyl diacrylate, 0.05 wt % of benzoyl peroxide, 30 wt % of propylene carbonate (PC), 10 wt % of ethylene carbonate (EC), 10 wt % of diethyl carbonate (DEC), 30 wt % of ethyl methyl carbonate (EMC), 13.95 wt % of fluoroethylene carbonate (FEC), and 1 wt % of vinylene carbonate (VC) were uniformly mixed to obtain a transparent liquid, and a mixture of lithium hexafluorophosphate and lithium bistrifluoromethylsulfonyl imide (the mixing mass ratio of lithium hexafluorophosphate and lithium bistrifluoromethylsulfonyl imide was 9:1) was added to the transparent liquid for dissolution to obtain an electrolyte precursor solution having a lithium salt concentration of 1.5 mol / L;
[0112] The positive electrode sheet obtained in step 1) and the negative electrode sheet obtained in step 2) are rolled, slit, and sheeted, and then wound with a separator, welded, and packaged. An electrolyte precursor solution is injected, and the electrolyte precursor solution is pre-polymerized at 40°C for 0.5h and then heated to 100°C for polymerization for 6h to complete curing. The cured battery system is then charged to a cutoff voltage of 4.2V at 90°C, 5MPa pressure, and 0.3C rate for formation treatment. After formation, sorting and secondary packaging are performed to obtain the battery of this embodiment.
[0113] Examples 2 to 6 and Comparative Example 1
[0114] The preparation methods of the batteries of Examples 2 to 6 and Comparative Example 1 are basically the same as those of Example 1, except that the positive electrode slurry formulation, negative electrode slurry formulation, electrolyte precursor solution composition (excluding lithium salt), curing conditions, and formation conditions are different. The specific differences are listed in Table 1.
[0115] Table 1
[0116] Test example
[0117] 1. XRD test
[0118] The batteries of Examples 1 to 6 and Comparative Example 1 were disassembled to obtain electrolytes. The electrolytes were washed with deionized water and then vacuum-treated at 80°C for 48 hours to reduce the moisture content to less than 1000 ppm. XRD tests were then performed at test angles of 10° to 90°. The test results are shown in Figures 1 to 7.
[0119] Figure 1 is an X-ray diffraction pattern of the electrolyte of Example 1, Figure 2 is an X-ray diffraction pattern of the electrolyte of Example 2, Figure 3 is an X-ray diffraction pattern of the electrolyte of Example 3, Figure 4 is an X-ray diffraction pattern of the electrolyte of Example 4, Figure 5 is an X-ray diffraction pattern of the electrolyte of Example 5, Figure 6 is an X-ray diffraction pattern of the electrolyte of Example 6, and Figure 7 is an X-ray diffraction pattern of the electrolyte of Comparative Example 1.
[0120] 1 to 7 , the diffraction peaks and their half-peak widths appearing in the X-ray diffraction patterns of the electrolytes of Examples 1 to 6 and Comparative Example 1 are listed in Table 2.
[0121] Table 2
[0122] As shown in Table 2, the electrolyte of Example 1 has 7 first diffraction peaks and 8 second diffraction peaks, the sum of the half-peak widths a of the 7 first diffraction peaks is 1.2792, the sum of the half-peak widths b of the 8 second diffraction peaks is 1.6375, and b / a=1.2801.
[0123] The electrolyte of Example 2 has 7 first diffraction peaks and 8 second diffraction peaks. The sum of the half-peak widths a of the 7 first diffraction peaks is 1.2792, the sum of the half-peak widths b of the 8 second diffraction peaks is 2.2512, and b / a=1.7598.
[0124] The electrolyte of Example 3 has 6 first diffraction peaks and 6 second diffraction peaks. The sum of the half-peak widths a of the 6 first diffraction peaks is 1.25338, the sum of the half-peak widths b of the 6 second diffraction peaks is 1.3305, and b / a=1.0615.
[0125] The electrolyte of Example 4 has 6 first diffraction peaks and 6 second diffraction peaks. The sum of the half-peak widths a of the 6 first diffraction peaks is 0.8954, and the sum of the half-peak widths b of the 6 second diffraction peaks is 1.6374b / a=1.8287.
[0126] The electrolyte of Example 5 has 8 first diffraction peaks and 6 second diffraction peaks, the sum of the half-peak widths a of the 8 first diffraction peaks is 1.1, the sum of the half-peak widths b of the 6 second diffraction peaks is 1.2792, and b / a=1.1629.
[0127] The electrolyte of Example 6 has 6 first diffraction peaks and 7 second diffraction peaks. The sum of the half-peak widths a of the 6 first diffraction peaks is 1.356, the sum of the half-peak widths b of the 7 second diffraction peaks is 1.7397, and b / a=1.2830.
[0128] The electrolyte of Comparative Example 1 has 4 first diffraction peaks and 3 second diffraction peaks, the sum of the half-peak widths a of the 4 first diffraction peaks is 1.535, the sum of the half-peak widths b of the 3 second diffraction peaks is 1.507, and b / a=0.9818.
[0129] 2. Conductivity test
[0130] The batteries of Examples 1 to 6 and Comparative Example 1 were disassembled to obtain electrolytes. The conductivity of the electrolytes of Examples 1 to 6 and Comparative Example 1 was tested using a blocking electrode method. The test results are shown in Table 3.
[0131] 3. Rate performance
[0132] The performance tests of the batteries of Examples 1 to 6 and Comparative Example 1 were performed at rates of 0.2C, 0.5C, 1C, 1.5C, and 2C, respectively. The test method was as follows: the battery was placed at 25°C for 5 minutes, then discharged at a rate of 0.5C to the lower limit voltage, and then placed for 5 minutes, then charged at a rate of 0.5C to the upper limit voltage, and then charged at a constant voltage at the upper limit voltage until the cutoff current was 0.05C. After further placing for 5 minutes, the battery was discharged at rates of 0.2C, 0.5C, 1C, 1.5C, and 2C to the lower limit voltage, and the discharge capacity at different rates was recorded, and the capacity retention rate of the battery after discharge at a rate of 0.2C was marked as 10 0%, and calculate the battery capacity retention rates after 0.5C, 1C, 1.5C, and 2C rate discharge, respectively. Among them, the capacity retention rate after 0.5C rate discharge = 0.5C rate discharge capacity / 0.2C rate discharge capacity × 100%, the capacity retention rate after 1C rate discharge = 1C rate discharge capacity / 0.2C rate discharge capacity × 100%, the capacity retention rate after 1.5C rate discharge = 1.5C rate discharge capacity / 0.2C rate discharge capacity × 100%, and the capacity retention rate after 2C rate discharge = 2C rate discharge capacity / 0.2C rate discharge capacity × 100%. The specific results are shown in Table 4.
[0133] 4. Discharge performance at different temperatures
[0134] The discharge performance of the batteries of Examples 1 to 6 and Comparative Example 1 was tested at 25°C, 45°C, 60°C, 10°C, 0°C, -10°C, and -20°C, respectively. The test method was as follows: after the battery was placed at 25°C for 5 minutes, it was discharged at a rate of 0.5C to the lower limit voltage, and after further placing it for 5 minutes, it was charged at a rate of 0.5C to the upper limit voltage, and charged at a constant voltage at the upper limit voltage until the cut-off current was 0.05C. The battery was placed at 25°C, 45°C, 60°C, 10°C, 0°C, -10°C, and -20°C for 30 minutes, and then discharged at a rate of 0.5C to the lower limit voltage. The discharge capacity after placing it at different temperatures for 30 minutes was recorded, and the battery capacity retention rate after discharging at 25°C for 30 minutes was marked. The battery capacity retention rate after discharge at 45°C, 60°C, 10°C, 0°C, -10°C and -20°C for 30 min was recorded as 100%, and the battery capacity retention rate after discharge at 45°C, 60°C, 10°C, 0°C, -10°C and -20°C for 30 min was calculated respectively, where: 45°C capacity retention rate = 45°C discharge capacity / 25°C discharge capacity × 100%, 60°C capacity retention rate = 60°C discharge capacity / 25°C discharge capacity × 100%, 10°C capacity retention rate = 10°C discharge capacity / 25°C discharge capacity × 100%, 0°C capacity retention rate = 0°C discharge capacity / 25°C discharge capacity × 100%, -10°C capacity retention rate = -10°C discharge capacity / 25°C discharge capacity × 100%, and -20°C capacity retention rate = -20°C discharge capacity / 25°C discharge capacity × 100%. The specific results are shown in Table 5.
[0135] 5. Thermogravimetric analysis
[0136] The batteries provided in the examples and comparative examples were disassembled, and the electrolytes were washed with deionized water. The solid phase components were collected after washing and dried at 100°C for 24 hours. The electrolytes were then subjected to thermogravimetric testing. When the initial temperature T0 was 25°C, the initial mass of the electrolyte was M0. The temperature was then increased at a rate of 5°C / min. At different temperatures T d The mass M of the electrolyte tested at the node is at a maximum temperature of 600° C. Thermogravimetric mass retention = 100%*(M / M0). The test results are shown in Table 6.
[0137] Table 3
[0138] As can be seen from Table 3, the electrolyte of the present application has good electrical conductivity, and the electrical conductivity can reach 5.0 mS / cm~7.0 mS / cm. By comparing Example 1 with Comparative Example 1, it can be seen that no prepolymerization is carried out in the process of preparing the electrolyte. The crystallization properties of the electrolyte obtained by prepolymerization are different, and the conductivity of the electrolyte obtained without prepolymerization is significantly worse.
[0139] Table 4
[0140] As can be seen from Table 4, the battery of the present application has good discharge performance when discharged at different rates. In particular, by comparing Example 4 with Comparative Example 1, it can be seen that as the discharge rate increases, the discharge advantage of the battery of the present invention becomes more obvious.
[0141] Table 5
[0142] As can be seen from Table 5, the battery of the present application has good discharge performance when discharged under different temperature environments. In particular, by comparing Example 4 with Comparative Example 1, it can be seen that as the temperature decreases, the discharge advantage of the battery of the present invention becomes more obvious.
[0143] Table 6
[0144] As can be seen from Table 6, the electrolyte of the present application has a certain stability at different temperatures and can meet the requirements for safe use of batteries.
[0145] The above describes the implementation methods of the present application. However, the present application is not limited to the above implementation methods. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrolyte, wherein The electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in an X-ray diffraction pattern, M≥1, N≥1; Among them, 10°≤x≤30°, 30°<y≤50°; The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.0≤b / a≤1.
9.
2. The electrolyte according to claim 1, wherein 0.8≤a≤1.4, 1.2≤b≤2.
3.
3. The electrolyte according to claim 1 or 2, wherein 1.1≤b / a≤1.
28.
4. The electrolyte according to any one of claims 1 to 3, wherein The conductivity of the electrolyte is 4mS / cm to 12mS / cm; Preferably, the conductivity of the electrolyte is 5-12 mS / cm.
5. The electrolyte according to any one of claims 1 to 4, wherein The electrolyte includes a polymer formed by polymerization of a first monomer and / or a second monomer; The first monomer includes at least three reactive functional groups; The second monomer includes two reactive functional groups.
6. The electrolyte according to claim 5, wherein The first monomer is selected from one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives, and dipentaerythritol hexaacrylate and its derivatives.
7. The electrolyte according to claim 5 or 6, wherein The second monomer is selected from one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, ethoxylated bisphenol A diacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, neopentyl glycol diacrylate and its derivatives, and 1,5-pentanediol diacrylate and its derivatives.
8. The electrolyte according to any one of claims 5 to 7, wherein The electrolyte includes 0.05 wt % to 9 wt % of a polymer and 91 wt % to 99.5 wt % of an electrolyte.
9. The electrolyte according to claim 8, wherein The electrolyte includes a lithium salt and an organic solvent. Preferably, the organic solvent includes a cyclic carbonate, a linear carbonate and / or a linear carboxylate.
10. The electrolyte according to any one of claims 1 to 9, wherein The weight loss rate of the electrolyte within the temperature range of 25° C. to 100° C. does not exceed 4%.
11. The electrolyte according to claim 10, wherein The weight loss rate of the electrolyte within the temperature range of 25° C. to 600° C. does not exceed 84%.
12. The electrolyte according to claim 10 or 11, wherein The temperature of the electrolyte with a mass of M0 is raised from 25°C at a heating rate of 5°C / min. d The mass M d Satisfy at least one of the following: (1) When the temperature T d When the temperature reaches 25-100℃, the mass of the electrolyte M d ≥92.21%*M0; (2) When the temperature T d When the temperature reaches 25℃~200℃, the mass M of the electrolyte d ≥47.63%*M0; (3) When the temperature T d When the temperature reaches 25℃~300℃, the mass M of the electrolyte d ≥33.41%*M0; (4) When the temperature T d When the temperature reaches 25℃~400℃, the mass M of the electrolyte d ≥25.53%*M0; (5) When the temperature T d When the temperature reaches 25℃~500℃, the mass M of the electrolyte d ≥17.21%*M0; (6) When the temperature T d When the temperature reaches 25℃~590℃, the mass of the electrolyte M d ≥15.54%*M0.
13. The electrolyte according to any one of claims 5 to 7, wherein The polymer is prepared by a method comprising the following steps: Prepolymerizing a mixed system including the first monomer and / or the second monomer at 40° C. to 60° C. and then heating the system to 80° C. to 100° C. to perform polymerization to obtain the polymer; Wherein, the prepolymerization reaction time is 0.2h to 2h, and the polymerization reaction time is 0.5h to 6h.
14. A battery, wherein: The electrolyte comprises the electrolyte according to any one of claims 1 to 13.
15. The battery according to claim 14, wherein: The battery is a semi-solid battery or a solid battery.
16. The battery according to claim 14 or 15, wherein: The battery is prepared by a method comprising the following steps: Performing a formation treatment on a battery system including the electrolyte to obtain the battery; The formation treatment comprises: charging the battery system including the electrolyte to a cut-off voltage at a temperature of 60° C. to 90° C., a pressure of ≤5 MPa, and a rate of ≤0.3C.
17. The battery according to any one of claims 14 to 16, wherein: It also includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.
18. The battery according to any one of claims 14 to 17, wherein: It also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes silicon, silicon carbon, SiO x , lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, copper nitride, etc.